Peran Manajemen Pemasaran Pada Aplikasi Quipper Sebagai Media Pembelajaran Siswa: Studi Literatur - Ageng Saepudin Kanda S; Siti Zakiyya Nur Aulia Kurniawan (Jurnal Bintang Manajemen, 2024)
The rapid advancement of technology supports the development of learning. One of them is the use of learning media using e-learning. The Quipper application can be used as a learning media that utilizes technological developments. The purpose of this research is to provide valuable insights to Quipper organizers and stakeholders to improve the effectiveness of marketing and application management and improve the quality of student learning. The method used is a literature study. The results of the study are The role of marketing management in the Quipper application is to market the company's products to achieve long-term profit levels. This application aims to improve the quality of education and improve the education gap by providing learning media that is easy to learn.